The influence of extensive reading on junior high school students' reading motivation and reading performance in Taiwan - Wu, Jiaying, author; Doug, Flahive, advisor; Ehlers-Zavala, Fabiola, committee member; Sprain, Leah, committee member (Colorado State University. Libraries, 2012)
Researchers of second language learning have pointed out that the strategies students use in learning a foreign language can affect their reading motivation and performance in second language acquisition. As an important means of providing second language learners with systematic reading materials, extensive reading is an approach that involves a wide range of original and interesting cultures as well as linguistic phenomena which prompt reading motivation and enhance reading performance of learners. However, reading motivation and reading performance are both of multiple dimensions, and thus far it is unclear which of the dimensions can be influenced by extensive reading. This research focuses on the influence of extensive reading on junior high school students' reading motivation and reading performance. A motivational questionnaire and an English reading test were used for data collection. A total of 69 8th graders took part in this study. These participants, who have been learning English at school for formal English education for four and a half years, were divided into the experimental group and the control group. The two groups did not significantly differ with regard to scores in mid-term and final English exams. Both of the experimental and control groups took pretests of reading motivation and reading performance. Then the experimental group was given the opportunity to read just for pleasure by selecting at least one book from four graded books (such as Let Me Out!). For the experimental group, the instruction time was forty-five minutes for each class period twice a week which lasted for one and half month for the total six weeks. The control group was assigned the textbook Let's talk in English and were required to memorize five words appearing in the article after each class and a short passage. Six weeks later, both control and experimental groups took posttests for reading motivation and reading performance. Then six interviewees were asked their attitudes towards extensive reading. Independent t tests were used for statistical analyses. The major findings are as follows: 1) Extensive reading did not influence reading seven dimensions of reading motivation (the target of taking pride, reading efficacy, interest in English reading, self-efficacy, reading for grade, intrinsic interest, and extrinsic motivation).Unfortunately, extensive reading increased avoidance of English reading. 2) Extensive reading enhanced vocabulary recognition, reading performance and general performance. The results arising from this study have important implications for both the learning and teaching of English as a second language.
Keywords: extensive reading; second language acquisition; reading performance; reading motivation